Telaah Makna Qurrata A’yun dalam Al-Qur’an sebagai Cerminan dari Keluarga Sakinah - Umam, Khoirul Safril; Nasrullah, Nasrullah; Khoiron, Fattah; Idrisa, Zair; Salim, Agus (UIN Syarif Hidayatullah Jakarta, 2024)
A study on the meaning of Qurrata A'yun is crucial as it remains a subject of ongoing debate. This paper aims to comprehend the meaning of Qurrata A'yun as a reflection of the Sakinah family concept. Employing a qualitative descriptive method with a library research approach, data was gathered by analyzing primary sources and classified based on their categorization. Data analysis was conducted using Miles and Huberman's techniques of data reduction, data presentation, and conclusion drawing. The findings reveal that Qurrata A'yun signifies a spouse or offspring who brings solace to the heart and eyes upon sight, fostering a harmonious and peaceful family environment. The concept of the Sakinah family and the meaning of Qurrata A'yun are interconnected, both indicating a harmonious family characterized by love and a strong connection with God.